Biomarkers for Predicting Abiraterone Treatment Outcome and Selecting Alternative Therapies in Castration‐Resistant Prostate Cancer. Issue 6 (12th April 2022) - Qin, Sisi; Gao, Huanyao; Kim, Wootae; Zhang, Huan; Gu, Yayun; Kalari, Krishna R.; Sinnwell, Jason P.; Scholz, Jodi A.; Xie, Fang; Yin, Ping; Yu, Jia; Qin, Bo; et al.
Abstract : Approximately one‐third of patients with metastatic castration‐resistant prostate cancer (CRPC) exhibited primary abiraterone resistance. To identify alternative treatment for abiraterone nonresponders, we performed drug discovery analyses using the L1000 database using differentially expressed genes identified in tumor biopsies and patient‐derived xenograft (PDX) tumors between abiraterone responders and nonresponders enrolled in PROMOTE trial. This approach identified 3 drugs, including topoisomerase II (TOP2) inhibitor mitoxantrone, CDK4/6 inhibitor palbociclib, and pan‐CDK inhibitor PHA‐793887. These drugs significantly suppressed the growth of abiraterone‐resistant cell lines and PDX models. Moreover, we identified 11 genes targeted by all 3 drugs that were associated with worse outcomes in both the PROMOTE and Stand Up To Cancer cohorts. This 11‐gene panel might also function as biomarkers to select the 3 alternative therapies for this subgroup of patients with CRPC, warranting further clinical investigation.